The Female Athlete’s Heart: Overview and Management of Cardiovascular Diseases - Silvia Castelletti; Sabiha Gati (European Cardiology Review)
The number of female athletes taking part in elite and amateur sport is ever increasing. In contrast with male athletes, few studies have focused on cardiovascular adaptations to exercise in women, the effects of lifelong exercise on heart muscle and electrical tissue, the risk of exercise-related sudden cardiac death and the management of cardiovascular disease. Women have a lower prevalence of large QRS complexes, repolarisation changes including inferior and lateral T-wave inversion, and cardiac dimensions exceeding predicted limits compared with men. The risk of exercise-related sudden cardiac death is significantly lower in women than men. Also, women who have engaged in lifelong exercise do not have a higher prevalence of AF, coronary artery calcification or myocardial fibrosis than their sedentary counterparts. Apart from providing an overview of the existing literature relating to cardiac adaptations, this review explores possible reasons for the sex differences and focuses on the management of cardiovascular disorders that affect female athletes.